Two men in front of a log cabin in the Klondike, ca. 1898 - Hegg, Eric A., 1867-1948
In the Yukon Territory, miners and others cut most of the tree cover from nearby hillsides to fuel fires and to build buildings and sluices. This photo, taken around 1898, shows two men in front of a log cabin, possibly in Dawson. There are few trees left in the area surrounding the cabin. 1 photographic print: b&w; 8 x 10 in.